EVALUATION OF SOME BIOLOGICAL AGENTS AS AN INTEGRATED PESTMANAGEMENT COMPONENTS TO CONTROL CUCCURBIT FRUIT FLY (LEOW) Dacus ciliatus AND MELON FRUIT FLY Dacus frontalis (Beker) ON CUCUMBER. - & Al-Jorany, Al Shalchi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study aimed to evaluate the efficacy of some biological agents like commertial product Richarge which contained basically from Beauveria bassiana and Metarhizium anisoplae in addition to fungal isolate of Lecanilicium lecanii and Metarizhium spp. and insecticide Telstar at field experiment. The infestation percentage on cucumber fruits was very high 100% in all treatment at the beginning of fruit formation during 1st week of October 2015, meanwhile its reached the lowest level on third week of October were 18.67% in Recharge, 28% in Meta 107 and 37.33% in the control. The results showed that the number of infested fruits was reduced in next harvesting from 25 infested fruits until reached 4.67, 4.67, 6.33, 7, 7, 7 and 7.67 infested fruit/ sample for Recharge, Meta 107, Meta 105 ، Telstar ، Lecani 107 ، Lecani 105 and control respectively after five weeks of control that because of effect of biological and chemical agents in pest population reduction which approved by increasing of fungal colonies forming units (CFU). Treatment with Recharge had a rule in crop saved reached 16.37% from total crop harvest.